Effects of Different Bud Thinning Methods on Nutritional Quality and Antioxidant Activities of Fruiting Bodies of Pleurotus eryngii - Liu, Lingyun; Wang, Lupeng; Li, Xuefei; Zhu, Shurui; Pan, Niangang; Wang, Xin; Li, Changtian; Li, Yu (Frontiers in Plant Science, 2022)
The cultivation of Pleurotus eryngii was studied by different methods, such as puncturing and fixed-point mushroom production, shading treatment at the top of the bag, and pulling the top of the bag. The agronomic characters, yield, nutritional components, and antioxidant activities in vitro of fruiting bodies of P. eryngii were determined. The results showed that the number of buds in the perforated treatment was less than that in the traditional fruiting bodies production method to a certain extent. When a circular hole with a diameter of 1.5 cm was drilled in the perforated treatment, the number of buds was less than that in the control group. The efficiency of artificial removal of buds was significantly higher than that of the control group, but the harvesting date was longer than that of other methods. The number of buds in shading treatment and bag opening treatment was significantly less than that in the control group, which could effectively control the number of buds and reduce the cost of manpower and material resources. In terms of nutritional components, the A3 treatment group with a hole diameter of 1.0 cm and a quantity of one had the highest crude protein content and a significant difference in crude fiber content compared with other treatments. The extraction rate of B5 crude polysaccharide was the highest, and the extraction rate was 12.90%. The antioxidant activities in vitro increased with the increase of crude polysaccharide concentration. Using A3 treatment to cultivate fruiting bodies is conducive to meeting people's requirements for quality of life.